Escaping the Self: Identity, Group Identification and Violence - James Hardie-Bick (Oñati Socio-Legal Series)
This article draws on the early work of Erich Fromm. In Escape from Freedom Fromm (1969 [1941]) directly addressed the psychological mechanisms of escape modern individuals employ to protect themselves from feelings of ontological insecurity and existential estrangement. The article builds on Fromm’s analysis by discussing the significance of his escape mechanisms for understanding the dynamic psychological attractions of identifying with entitative groups. Fromm’s work will be discussed in relation to Hogg’s recent work on uncertainty-identity theory. The aim of the article is to examine the advantages of combining Fromm’s psychoanalytic analysis with Hogg’s uncertainty-identity theory and to highlight the potential this approach has for understanding why groups engage in violent and destructive behaviour.